Sharia Corporate Governance and Reputation Effects on Customer Trust in Islamic Bank (Survey on BJB Syariah KCP Cimahi) - Evita Nurul Rusady; Girang Razati; Suci Aprilliani Utami (Universitas Pendidikan Indonesia, 2019)
The city of Cimahi is ranked the lowest in wealth and deposits compared to eight cities in West Java Province, which confirms that the level of public trust in Islamic banks is still low. Another factor that causes low customer confidence is that the Sharia Corporate Governance has not been maximized, as evidenced by IRTI's research results showing that GCG implementation has not been implemented well in Islamic banks in various countries and failure to apply sharia principles to 85%. Sharia Corporate Governance (SCG) combines two theories, namely Good Corporate Governance (GCG) and the theory of Sharia Compliance. The implementation of SCG in Islamic banks is based on six principles: transparency, accountability, accountability, professionalism and fairness, and implementation of compliance shariah. Sharia Corporate Governance (SCG) can also be referred to as a system, regulation, and process used to realize a compliance culture in managing Islamic banking risk as well as monitoring, regulating, and encouraging its performance efficiently to generate sustainable added value for stakeholders in the long term following sharia principles. This study aims to determine the effect of the application of SCG and reputation on customer trust in Islamic banks. The population in this study is the customer of BJB Syariah KCP Cimahi. The sampling technique in this study was simple random sampling with a sample of 210 respondents. The method used in this research is the explanatory method. The data analysis technique used is the multiple linear regression method. The results of the research designation that the implementation of Sharia Corporate Governance and reputation simultaneously affect customer trust, which will increase the market share of Islamic banks.